2023
DOI: 10.1177/03946320231189993
|View full text |Cite
|
Sign up to set email alerts
|

Use of canakinumab and remdesivir in moderate-severe COVID-19 patients: A retrospective analysis

Abstract: Objectives: The dysregulated immune response occurring upon COVID-19 infection can lead to tissue damage and organ failure. Different therapeutic strategies are needed to cope with the current and future outspread of COVID-19, including antiviral and anti-inflammatory agents. We describe the outcome of hospitalized patients treated with canakinumab and remdesivir plus the standard of care therapy. Methods: This observational study describes the outcome of the combination of canakinumab (450 mg for patients ≥40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…In our patients, after RDV therapy, we have found reduced levels of inflammatory markers, such as IL-6, fibrinogen, D-dimer, and ferritin (see Supplementary Table S1). In the same way, in a recent study, it has been demonstrated that combination treatment with human monoclonal anti-IL-1β antibody, remdesivir, and steroids in moderate-to-severe hospitalized COVID-19 patients can reduce inflammatory markers [18]. The adaptive immune system represented by B and T cells show various effects in the cytokine storm [19].…”
Section: Discussionmentioning
confidence: 85%
“…In our patients, after RDV therapy, we have found reduced levels of inflammatory markers, such as IL-6, fibrinogen, D-dimer, and ferritin (see Supplementary Table S1). In the same way, in a recent study, it has been demonstrated that combination treatment with human monoclonal anti-IL-1β antibody, remdesivir, and steroids in moderate-to-severe hospitalized COVID-19 patients can reduce inflammatory markers [18]. The adaptive immune system represented by B and T cells show various effects in the cytokine storm [19].…”
Section: Discussionmentioning
confidence: 85%